BATALNYA PERKAWINAN KARENA MURTAD DI TINJAU DARI HUKUM ISLAM - Chamim, M; Rohim, Mif (Irtifaq, 2019)
This article aims to examine the views of Islamic scholars related to thecancellation of marriage (fasakh) because of apostasy and the legal consequencescaused. Cancelation of Marriage (fasakh) happens later, there is a reason thatprevents the perpetuation of marriage or is a consequence of knowing somethingthat accompanies the contract, which makes the contract invalid. At the sametime, the cancellation of the marriage itself has the legal consequence of it. One ofthe consequences is related to the legal consequences of the child and the jointproperty of the marriage, one of which is apostasy. The legal consequences thatoccur due to the conversion of religion (apostasy) to one Muslim couple have twomajor effects on the child and on the common property. While the status of thechild the author concludes that the child who is one of his parents is an apostate,the child is rested on his mother. As for assets, they acquired prior to apostasy and it can be divided equally between two sides, but if the assets obtained afterapostasy, then there is no right for anyone to share. Keywords: Islamic law, cancellation of marriage, apostasy